2011
DOI: 10.1088/0741-3335/53/2/025012
|View full text |Cite
|
Sign up to set email alerts
|

Validity of quasilinear theory: refutations and new numerical confirmation

Abstract: The validity of quasilinear (QL) theory describing the weak warm beam-plasma instability has been a controversial topic for several decades. This issue is tackled anew, both analytically and by numerical simulations which benefit from the power of modern computers and from the development in the last decade of Vlasov codes endowed with both accuracy and weak numerical diffusion. Self-consistent numerical simulations within the Vlasov-wave description show that QL theory remains valid in the strong chaotic diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 49 publications
(69 citation statements)
references
References 48 publications
2
67
0
Order By: Relevance
“…This brings a small spatial modulation to the particle density which provides a source term for the Langmuir waves. However, if the plateau is broad, the evolution of the wave spectrum is slow, which brings only a small change to the previous simplistic picture of a uniform density (see section 2.2 of [15]). Therefore, there is almost no density fluctuation to drive the wave evolution as defined by the self-consistent dynamics: the wave spectrum is frozen.…”
Section: Dynamics When the Distribution Is A Plateaumentioning
confidence: 84%
See 4 more Smart Citations
“…This brings a small spatial modulation to the particle density which provides a source term for the Langmuir waves. However, if the plateau is broad, the evolution of the wave spectrum is slow, which brings only a small change to the previous simplistic picture of a uniform density (see section 2.2 of [15]). Therefore, there is almost no density fluctuation to drive the wave evolution as defined by the self-consistent dynamics: the wave spectrum is frozen.…”
Section: Dynamics When the Distribution Is A Plateaumentioning
confidence: 84%
“…However, the simulations brought an unexpected clue to elucidate it: the variation of the phase of a given wave with time was found to be almost non fluctuating with the random realizations of the initial wave phases [16]. Therefore the simulations showed that the randomness of the final wave phases was a mere consequence of that of initial phases.…”
Section: E a Crucial Numerical Simulationmentioning
confidence: 95%
See 3 more Smart Citations